Differential glycaemic control with basal insulin glargine 300 U/mL versus degludec 100 U/mL according to kidney function in type 2 diabetes: A subanalysis from the BRIGHT trial. Issue 8 (28th April 2020) - Haluzík, Martin; Cheng, Alice; Müller‐Wieland, Dirk; Westerbacka, Jukka; Bosnyak, Zsolt; Lauand, Felipe; Melas‐Melt, Lydie; Karalliedde, Janaka; Rosenstock, Julio; Bolli, Geremia B.
Abstract: Aims: Chronic kidney disease (CKD) challenges diabetes management and is associated with increased cardiovascular morbidity and mortality. We examined whether clinical outcomes with insulin glargine 300 U/mL (Gla‐300) and insulin degludec 100 U/mL (IDeg‐100) are affected by renal function in a prespecified subgroup analysis from the BRIGHT trial. Materials and methods: BRIGHT (NCT02738151) was a multicentre, open‐label, randomized, active‐controlled, two‐arm, parallel‐group, 24‐week study in insulin‐naïve uncontrolled type 2 diabetes (T2D). Participants were randomized 1:1 to evening Gla‐300 (n = 466) or IDeg‐100 (n = 463) and stratified based on baseline estimated glomerular filtration rate (eGFR) for this analysis. Results: Heterogeneity of treatment effect across renal function subgroups was observed ( P = .02), reflecting a greater mean glycated haemoglobin (HbA1c) reduction from baseline to week 24 with Gla‐300 versus IDeg‐100 in the eGFR <60 mL/min/1.73 m 2 subgroup (least squares mean difference: −0.43% [95% confidence interval: −0.74% to −0.12%]), while there were no differences in hypoglycaemia incidence or rates over 24 weeks in that subgroup. HbA1c reductions were similar between treatments in the other eGFR subgroups. However, heterogeneity was observed for annualized rates of anytime (24 hours) or nocturnal (00:00‐05:59 hours) confirmed hypoglycaemia (≤70 mg/dL [≤3.9 mmol/L]) over 24 weeks showing less hypoglycaemia with Gla‐300 versus IDeg‐100 in the ≥90 mL/min/1.73 m 2 . Conclusions: Kidney function seems to affect the glucose‐lowering effects of Gla‐300 versus IDeg‐100 in insulin‐naïve T2D. Greater HbA1c reductions with Gla‐300 without increase in hypoglycaemia risk, were observed in patients with eGFR <60 mL/min/1.73 m 2 .